Pharmacological Activities of Citrus hystrix - Puji Kurniawati Rahman; Hamiseh; Teguh Setiawan Wibowo (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
Kaffir lime (Citrus hystrix) is a bushy, small and bushy plant which is mainly used for its fruit and leaves as a seasoning for cooking. Kaffir lime (Citrus hystrix) belongs to the Rutaceae family. Internationally, kaffir lime (Citrus hystrix) is known as "kaffir lime". Kaffir lime (Citrus hystrix) grows in the tropics and originates from Southeast Asia, India, Malaysia and China and is widely used in the Netherlands, Germany, France, Italy and Spain. Kaffir lime (Citrus hystrix) is also very popular as a medicine which is important in treating various diseases. In this article, the discussion on kaffir lime (Citrus hystrix) is focused on its chemical composition and medical value, especially on its pharmacological activities such as antimicrobial, anti-inflammatory, antioxidant, antitumor, antilarvae, and antifertility as well as the use of kaffir lime (Citrus hystrix) as orthodox medicine and its applications traditional.